2013
DOI: 10.1111/ppa.12067
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of low levels of genetic diversity for the Phytophthora austrocedrae population in Patagonia, Argentina

Abstract: Phytophthora austrocedrae is a recently discovered pathogen that causes severe mortality of Austrocedrus chilensis in Patagonia. The high level of susceptibility of the host tree, together with the distribution pattern of the pathogen, have led to the hypothesis that P. austrocedrae was introduced into Argentina. The aim of this study was to assess the population structure of P. austrocedrae isolates from Argentina in order to gain an understanding of the origin and spread of the pathogen. Genetic diversity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 33 publications
0
18
0
2
Order By: Relevance
“…There is an accumulating body of indirect and partly also direct evidences that P. cinnamomi , P. lateralis , P. plurivora and P. ramorum originate from Southeast and eastern Asia ( Shearer & Tippett 1989 , Brasier et al 1993 , 2010 , 2012 , Chang et al 1996 , Hansen et al 2000 , 2012 , Jung et al 2000 , 2016 , 2017a , b , c , Rizzo et al 2002 , Shearer et al 2004 , Goss et al 2009 , Hardham 2005 , Jung 2009 , Jung & Burgess 2009 , Brasier & Webber 2010 , Webber et al 2010 , 2012 , Franceschini et al 2014 , Arentz 2017 ). Also for P. agathidicida in New Zealand P. austrocedri in Argentina and the UK, P. acerina and P. cactorum in Europe, P. elongata in Australia, P. kernoviae in the UK, P. multivora in Australia and Europe, P. pinifolia in Chile, P. × cambivora in Europe and North America, and for the parents of P. × alni , i.e., P. × multiformis and P. uniformis , the high aggressiveness to native woody species, low genetic variability of pathogen populations and co-existence with healthy native vegetation in other continents, respectively, indicate exotic origin ( Crandall et al 1945 , Jung et al 2000 , 2002 , 2003b , 2016 , 2017b , c , Brasier & Kirk 2001 , Vettraino et al 2001 , 2005 , Jung & Blaschke 2004 , 2006 , Brasier et al 2005 , Greslebin et al 2007 , 2010 , Saavedra et al 2007 , Beever et al 2009 , Jung 2009 , Scott et al 2009 , Durán et al 2010 , Rea et al 2010 , Green et al 2013 , Vélez et al 2013 , Ginetti et al 2014 , Henricot et al 2014 , <...>…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an accumulating body of indirect and partly also direct evidences that P. cinnamomi , P. lateralis , P. plurivora and P. ramorum originate from Southeast and eastern Asia ( Shearer & Tippett 1989 , Brasier et al 1993 , 2010 , 2012 , Chang et al 1996 , Hansen et al 2000 , 2012 , Jung et al 2000 , 2016 , 2017a , b , c , Rizzo et al 2002 , Shearer et al 2004 , Goss et al 2009 , Hardham 2005 , Jung 2009 , Jung & Burgess 2009 , Brasier & Webber 2010 , Webber et al 2010 , 2012 , Franceschini et al 2014 , Arentz 2017 ). Also for P. agathidicida in New Zealand P. austrocedri in Argentina and the UK, P. acerina and P. cactorum in Europe, P. elongata in Australia, P. kernoviae in the UK, P. multivora in Australia and Europe, P. pinifolia in Chile, P. × cambivora in Europe and North America, and for the parents of P. × alni , i.e., P. × multiformis and P. uniformis , the high aggressiveness to native woody species, low genetic variability of pathogen populations and co-existence with healthy native vegetation in other continents, respectively, indicate exotic origin ( Crandall et al 1945 , Jung et al 2000 , 2002 , 2003b , 2016 , 2017b , c , Brasier & Kirk 2001 , Vettraino et al 2001 , 2005 , Jung & Blaschke 2004 , 2006 , Brasier et al 2005 , Greslebin et al 2007 , 2010 , Saavedra et al 2007 , Beever et al 2009 , Jung 2009 , Scott et al 2009 , Durán et al 2010 , Rea et al 2010 , Green et al 2013 , Vélez et al 2013 , Ginetti et al 2014 , Henricot et al 2014 , <...>…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenicity tests on seedlings, saplings and adult trees demonstrated high aggressiveness of P. austrocedri to A. chilensis confirming the association of this pathogen with the decline in Argentina ( Greslebin & Hansen 2010 ). The virtually clonal population structure of P. austrocedri and its aggressive behaviour on Cordilleran cypress, strongly suggested that it is an alien invasive pathogen in Argentina ( Vélez et al 2013 ).…”
Section: Soilborne Phytophthora Diseases In Forests and Woodlandsmentioning
confidence: 99%
“…In Argentina, mortality of A. chilensis was first detected in 1948 on Victoria Island which was known for its introduction of exotic woody plants from different continents. This has led to the view that P. austrocedri was introduced into that country on infected, imported plants (Vélez, Coetzee, Wingfield, Rajchenberg, & Greslebin, 2013). DNA of P. austrocedri has been found in diseased tissues of young Juniperus species, C. lawsoniana and Cupressus x leylandii imported into Britain from other European Union countries (J. Barbrook, Animal and Plant Health Agency, York, England, personal communication and A. Schlenzig, Science and Advice for Scottish Agriculture, Edinburgh, Scotland, personal communication) and in diseased J. communis plants located in nurseries and private gardens in England and Wales (Denton, Denton, Waghorn, & Henricot, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The ITS sequence of British isolates differs consistently from that of the Argentinian isolates, which themselves have very low levels of genetic diversity (Vélez et al ., ). Indeed the clonal nature and the aggressive behaviour of the pathogen on its host in Argentina indicate strongly that it has been introduced there (Vélez et al ., ). Thus the evidence so far points to P. austrocedrae having an unknown origin in a different location to the current known geographical areas of disease outbreak.…”
Section: Discussionmentioning
confidence: 97%